Practices Contributing to Healthy Longevity among Elderly Population in Ipoh, Perak - Durratul Hannah Hanaz Ismadi; Nur Farah Atikah Rosman; Nur Naili Nadiah Mohamad Shaiedi; Siti Nur Aisyah Zulkifly; Qistina Adilah Redzuan; Osman Ali (Asian Journal of Medicine & Health Sciences, 2024)
Background: Healthy longevity refers to living a long life while maintaining good health, influenced by genetics, lifestyles, and overall well-being. Aim: This study examines lifestyle, social, and spiritual practices contributing to longevity among elderly individuals aged 80 years and above in Perak.  Materials and method: A mixed method study was conducted, involving interviews of 5 elderly individuals aged 85 an above, for the qualitative component, and 55 elderly individuals were subjected to a self-administered questionnaire for the quantitative component. The questionnaires aimed to obtain information on sociodemographic and health information, along with details on lifestyle, social, and spiritual practices. Results: The study found that healthy aging and longevity were associated with proper diet, active living and adequate sleep. Early healthcare interventions helped reduce disease-related morbidity. Social interactions improved mental health, and high spirituality, including feelings of gratitude played a crucial role in well-being. Quantitative data showed 56.4% of respondents () had a normal body mass index (BMI), 61.8% were physically active. Most consumed rice regularly (78.2%), along with meat (89.1%), seafood (92.7%), dairy products (83.7%), vegetables (63.6%). and fruits (>80%). Majority never smoke (70.9%) or drink alcohol (76.4%). However, almost 90% had comorbidities, especially hypertension (78.2%), diabetes mellitus (56.4%) and dyslipidemia (54.5%), with 87.3% on medication and 76.4% showing good disease control. Most respondents had good relationships with relatives and friends (60%) and had moderate to high social engagements (more than 60%). High spirituality was practiced by 72%. Those under 85 had significantly higher social engagements (p